Plantaricin IIA-1A5 from lactobacillus plantarum IIA-1A5 displays bactericidal activity against staphylococcus aureus - Irma Isnafia Arief; Cahyo Budiman; Betty Sri Laksmi Jenie; Eryk Andreas; Yuneni, A (Wageningen Academic Publishers, 2015)
Plantaricin IIA-1A5 is a bacteriocin produced by Lactobacillus plantarum IIA-1A5 isolated from Indonesian beef. This research aimed to identify the genes involved in plantaricin IIA-1A5 production and examine its mode of action against Staphylococcus aureus. It has been reported that a bacteriocin structural gene, plnW, is present in genome of L. plantarum IIA-1A5. Here, we reported the presence of additional genes responsible for plantaricin precursor (plnA and plnEF) and a gene encoding the quorum sensor of histidine kinase (plnB). It indicates that genes involved in production of plantaricin IIA-1A5 are organized in at least two bacteriocin operons (plnABCD, plnEFI) and a structural plnW gene. Purified plantaricin IIA-1A5 yielded a single band in SDS-PAGE with apparent size of 6.4 kDa. Amino acid composition of purified plantaricin IIA-1A5 was mainly composed of cationic glutamic acid and cysteine that allowed the formation of disulphide bonds, suggesting plantaricin IIA-1A5 belongs to the pediocin-subclass of class II bacteriocins. Plantaricin IIA-1A5 displayed remarkable antibacterial activity against S. aureus, which was initiated by the adsorption of plantaricin IIA-1A5 onto the cell membrane of S. aureus. The adsorption is hypothesised to be facilitated by non-ionic interactions as it is reduced by the presence of organic solvents or detergents. This adsorption promoted leakage of cellular metabolites through the cell membrane of S. aureus, as indicated by the release of genetic and proteinaceous material of S. aureus observed at 260 and 280 nm, respectively. The leakage also promoted the release of divalent (Ca2+, Mg2+) and monovalent (K+) cations. The release of these intracellular components might be due to pores formed in the cell membrane of S. aureus by plantaricin IIA-1A5 as shown by scanning electron microscopy. Altogether, the mode of action of plantaricin IIA-1A5 against S. aureus seems to be bactericidal as indicated by lysis of the cell membrane.